Personal Branding Dharma Acarya Melalui Media Sosial YouTube - Artana, I Kadek; Ariasa Giri, I Made (Jayapangus Press, 2024)
This research discusses the personal branding of Dharma Acarya through YouTube Social Media. The aim of this research is to understand the form of personal branding of Dharma Acarya through YouTube social media and how Dharma Acarya implements the teachings of Hinduism through YouTube social media. This research employs a qualitative approach with a descriptive design. Data collection techniques involve interviews, observations, and documentation. The researcher collected data by observing videos on the personal YouTube channel of Dharma Acarya. This was done to gain an in-depth understanding of personal branding and the implementation of conveying the teachings of Hinduism through YouTube social media. The research findings reveal that various forms of personal branding and methods of implementing the teachings of Hinduism are adaptations to the evolving era, which facilitate effective communication through social media. Social media serves as a platform to build personal branding and convey the teachings of Hinduism. The teachings conveyed through YouTube social media encompass the literary teachings found in the Tri Hita Karana framework of Hinduism, yet the specific content varies among different Dharma Acaryas.